Второе.
16^(x+2)=4^(2(x+2)); 64=4^3;
Тогда исходное выражение примет вид: 4^(2(x+2))>=4^3. Основания равны, значит, 2(x+2)>=3, откуда, x+2>=3/2 и x>=-1/2
Первое.
25^(1/2)=5; (1/625)^(-1/2)=625^(1/2)=25; 32^(2/5)=(2^5)^(2/5)=2^2=4; 2^(-2)=1/2^2=1/4=0,25;
Всё вместе: 5+25+4+0,25=34,25
3/5 : 5/6 + 2 1/2 * 2/5 - 1 : 1 1/6 =
1) 3/5 : 5/6 = 18/25
2) 21/2 * 2/5 = 5/2 * 2/5 = 1
3) 1 : 1 1/6 = 1/1 : 7/6 = 6/7
4) 18/25 + 1 = 1 18/25
5) 1 18/25 - 6/7 = 151/175
-(8-x)-x=-8+x-x=-8
-----------------------------
(x-4)-(x+5)=x-4-x-5=-9
-----------------------------
-(y-a-3)-(4+a)=-y+a+3-4-a=-y-1
------------------------------
-(16-b+c)+(8+c)=-16+b-c+8+c=-8+b
-----------------------------
Ответ по действиям на фото.удачи!!!